Retail Credit Default Risk An Empirical Study - B.N, Dr. Shubha (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This study empirically examines the role of various socio -demographic and financial factors that determine borrowers default risk in housing loans. Using the data from the housing loan accounts (sanctioned from 1999-2010) of two public sector banks in Bangalore, the study investigates the repayment pattern of two groups of borrowers: defaulters and non-defaulters and group them into different risk level. The study uses stepwise regression to find the extent of influence of socio demographic and financial factors on default risk. The outcome of the study indicates that the association of financial variables like Net worth, Income, maturity and loan size are more significant on borrower default risk. However, one cannot ignore the sociodemographic variables like age, educational level, Number of dependents and experience in the job which otherwise may inhibit lender to properly assess credit risk in developing the internal score sheets. The outcome of the study shows that these parameters also act as default triggers.